Utilization and secondary use of waste oil and oil refining in the production of rubber - Turebekova, Gaukhar Z.; Pusurmanova, Gulzhamal Zn.; Sakibayeva, Saule A.; Sagitova, Guzalia F.; Dairabayeva, Aigul Zn.; Dosbayeva, Aidana M. (Journal of the Belarusian State University. Ecology, 2018)
This paper considers the most acute environmental problems of storage and disposal of wastes (sulfur and oil sludge), as well as some ways to solve them during oil extraction and refining. The Tengiz field produces a lot of sulfur waste, which is stored in open fields. Under the influence of the atmosphere, high temperature (in summer up to 45–50 °С), etc., there are formed many sulfur compounds, harmful to human health and the environment. By sequential study of influence on the properties of rubbers, composition of each of components separately (sulfur and oil sludge) with fixed amounts of other ingredients, optimization of the developed rubber compounds for production of a filler strip of tire beads has been carried out. Application of Tengiz sulfur allowed preserve kinetics of vulcanization, which could be decreased with application of organic part of the oil sludge. Also, use of Tengiz sulfur allowed increase the hardness of rubbers, which is necessary to increase the rigidity of the tire bead. The results of extended tests have shown the possibility to replace traditionally used in rubber compounds softeners with organic part of the oil sludge and use Tengiz sulfur as a vulcanizing agent. Fillers in the formulation of the rubber compounds for production of the filler strip can be partially replaced with a mineral part of the oil sludge.